PERTANGGUNGJAWABAN PIDANA PADA TINDAK PIDANA PERAMPASAN HAK ATAS TANAH (Analisis Putusan Nomor 12/Pid.B/2014/PN.Kbr dan Nomor 17/Pid.R/2010/PN.Kbr) - Bgr, Saifullah (LPPM Universitas Ekasakti Padang, 2019)
Crime art Deprivation of Land Rights is regulated among others in Article 385 of the Criminal Code with the threat of imprisonment for a maximum of 4 (four) years and also in Article 2 to Article 6 of Law Number 51 Prp Year 1960 with a maximum imprisonment of 3 (three) months and / or fines as much as Rp. 5,000, - (five thousand) rupiah. The problems described are, first, how is Criminal Accountability on Criminal Deprivation of Land Rights in Decision Number 12 / Pid.B / 2014 / PN.Kbr and Decisions Number 17 / Pid.R / 2010 / PN.Kbr, secondly how Judges Consideration in decides Criminal Case for Deprivation of Land Rights in Decision Number 12 / Pid.B / 2014 / PN.Kbr and Decision Number 17 / Pid.R / 2010 / PN.Kbr. The specification of this research is descriptive analytical, while the approach used is normative juridical, the data used is only secondary data collected through literature study, then analyzed qualitatively and presented in qualitative descriptive form. The first conclusion in the decision Number 12 / Pid.B / 2014 / PN.Kbr can be requested for criminal liability in accordance with Article 385 paragraph (4) of the Criminal Code, but the judge only decides for 3 (three) months, secondly on the decision Number 17 / P / R / 2010 / PN.Kbr pursuant to Article 6 paragraph (1) of Law Number 51 Prp Year 1960, but the judge decides 1 (one) month imprisonment.